2019
DOI: 10.1136/bmj.l1656
|View full text |Cite
|
Sign up to set email alerts
|

Association between Apgar scores of 7 to 9 and neonatal mortality and morbidity: population based cohort study of term infants in Sweden

Abstract: Objective To investigate associations between Apgar scores of 7, 8, and 9 (versus 10) at 1, 5, and 10 minutes, and neonatal mortality and morbidity. Design Population based cohort study. Setting Sweden. Participants 1 551 436 non-malformed live singleton infants, born at term (≥37 weeks’ gestation) between 1999 and 2016, with Apgar scores of ≥7 at 1, 5, and 10 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
65
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 26 publications
9
65
0
3
Order By: Relevance
“…We considered both gestational age and birthweight for gestational age as confounders, given that both influence umbilical artery blood gases at birth and Apgar score values in term infants. 8,9,22,24 Mode of delivery is also associated with metabolic acidosis 25 and reduced Apgar scores. 9 However, an emergency caesarean section or vaginal instrumental delivery may be caused by (confirmed or suspected) fetal asphyxia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We considered both gestational age and birthweight for gestational age as confounders, given that both influence umbilical artery blood gases at birth and Apgar score values in term infants. 8,9,22,24 Mode of delivery is also associated with metabolic acidosis 25 and reduced Apgar scores. 9 However, an emergency caesarean section or vaginal instrumental delivery may be caused by (confirmed or suspected) fetal asphyxia.…”
Section: Discussionmentioning
confidence: 99%
“…1,8 Within term (≥37 weeks) non-malformed infants with normal Apgar scores (7-10) at 1, 5, and 10 minutes, we recently found inverse associations between Apgar scores and risks of neonatal mortality and morbidity. 9 Reduced Apgar scores of 7-9 at 10 minutes were generally associated with the highest risks. We and others have reported similar findings with respect to Apgar scores within the normal range and risks of long-term outcomes, including CP and epilepsy, 2 autism, 10 developmental physical or emotional vulnerability in childhood, 11 and increasing needs of education in special schools.…”
Section: Anmentioning
confidence: 97%
See 1 more Smart Citation
“…In order to further understand the association between Apgar scores and the risk of adverse outcomes, particularly among those infants without obvious concerning clinical signs at the time of birth, Cnattingius and colleagues 6 have performed a series of studies over the past few years focused on the outcomes of infants with Apgar scores ≥7. Leveraging population data from Swedish national registries, they have demonstrated that infants with lower normal Apgar scores (7‐9) have an increased risk of neonatal morbidity and mortality, and long‐term adverse outcomes including cerebral palsy and epilepsy 7 relative to infants with an Apgar score of 10.…”
mentioning
confidence: 99%
“…These data seem to challenge the prevailing interpretation of Apgar scores of 7 or higher as “normal.” It should be kept in mind, however, that the absolute risk of neonatal mortality, cerebral palsy and epilepsy associated with low normal Apgar scores in the population of infants in these studies was small. For example, an Apgar score of 7 at 5 minutes was associated with a risk of neonatal death of 1 in 1000 6 and cerebral palsy of 3 in 1000 7 …”
mentioning
confidence: 99%